Evaluation Au Champ Du Potentiel De Croissance Et De La Production Du Riz (Oryza Sativa L.) Variété IR841 Inoculé En Pépinière Par Quatre Souches De Champignons Mycorhiziens À Arbuscules - Atama, Gnamkoulamba; Kodjo, Tounou Agbéko; Manguilibè, Tchao; Atti, Tchabi; Mawuko, Adjevi Anani Kossi; Komlan, Batawila (European Scientific Journal, ESJ, 2018)
The growth and production of rice (Oryza sativa L.) variety IR841 were evaluated in response to arbusular mycorrhizal fungus (AMF) inoculation. Four strains of AMF (Acaulospora spinosa, BEN 10, Glomus mosseae and G. hoi) were tested at 1.96 x 105 ; 3.91 x 105 and 7.82 x 10 5 spores/ha during two growing seasons 2016 and 2017, in a complete random block design. Uninoculated plants and plants fertilized with chemical fertilizer were used as control. The experiments conducted for 19 weeks including 5 weeks in nursery and 14 weeks in field tests showed better development and production of rice in inoculated plants compared to uninoculated controls. The tested rice variety was highly dependent on arbuscular mycorhization. For each strain the rate of mycorhization was dose dependent. The different growth parameters such as the height of the plant, the development of the root system, the total biomass, the number of tillers, the number of fertile panicles per plant, the number of paddy grains per panicle and the paddy grain yield, were positively correlated with the rate of root mycorhization. This study showed that biofertilizers based on mycorrhizal fungi provide important benefits to the plant, and can be used to improve the growth and yield of rice in Togo. The results are discussed in terms of usingAMF as alternative to chemical fertilizer in rice production system.